Independent risk factors of COVID-19 pneumonia in vaccinated Mexican adults - Efrén Murillo-Zamora; Ramón Alberto Sánchez-Piña; Xóchitl Trujillo; Miguel Huerta; Mónica Ríos-Silva; Oliver Mendoza-Cano (International Journal of Infectious Diseases, 2022)
Objectives: To evaluate host factors associated with the risk of coronavirus disease 2019 (COVID-19) pneumonia in vaccinated adults. Methods: A cohort study was conducted in Mexico, and data from 1607 adults with confirmed illness, with a positive history of COVID-19 vaccination, were analyzed. Risk ratios (RR) and 95% confidence intervals (CI) were computed as a measure of the significance of the associations between putative risk factors and the prevalence of COVID-19 pneumonia in vaccinated subjects. Results: The overall risk of pneumonia was 1.98 per 1000 person-days. In the multiple regression analysis, older subjects, those with a history of smoking (current), obesity, and type 2 diabetes mellitus were at increased risk of pneumonia. Conclusions: Our results suggest that the effectiveness of COVID-19 vaccines may be reduced in a subset of adults who are older aged, smokers, obese, or have type 2 diabetes mellitus.